Engaging fathers in the parenting of preschool children to address the phenomenon of fatherlessness - Azizah, Nurona; Sitopu, Yesenia Eliana; Wilis, Rafidah Rahajeng; Sudarwasih, Eni; Iriyanti, Ridha Nidia; Lailisya, Winda Nur (Caring: Jurnal Pengabdian Masyarakat, 2025)
Currently, parenting is closely associated with the mother figure. Fatherlessness is a condition where a child does not experience a father figure in their upbringing and daily life. A father has an important role in raising a child, such as participating in activities with them, providing emotional and physical support, teaching consistent discipline, and being a good role model. If the father's role is not fulfilled properly, it can lead to developmental issues in the child. The purpose of this Community Service Program (CSP) is to involve fathers in the upbringing of preschool children to address the phenomenon of fatherlessness. The design of the CSP included measuring the development of preschool children, inviting parents to fill out a questionnaire on father involvement in parenting, providing counselling on the importance of father involvement in parenting, informing the results of the questionnaire, and delivering the final report to PAUD (early childhood education) teachers. The program was conducted at a kindergarten in Malang City, with 126 respondents. The CSP results showed that most fathers spent 5–8 hours daily with their children, with high parental involvement (72%). Additionally, children's social development was classified as good. Thus, good father involvement significantly affects a child's social development.